ANALISIS KUALITAS PELAYANAN PEMBUATAN DOKUMEN KEPENDUDUKAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN PATI - Kusuma Ningrum, Renita Wahyu; Widowati, Nina; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2021)
One of the public services that is always attempted to be improved by the government is administration service. Public services are involved in such problems as the duration of the management of documents and infrastructure facilities are not adequate in serving the community. Disdukcapil Kabupaten Pati as one of civil registration provider in Pati regency has many problem accordin to Ombudsman’s Reports. This study aims to discover on how the quality of civil registration service and what factors are supporting and obstructing. The method used in this study is qualitative descriptive method. The data source in this study was obtained from interviews, observations, and documentation. Informant selection techniques are done using purposive sampling and accidental sampling. The quality of service is measured using five dimensions of Zeithaml theory, namely, tangible, reliability, responsiveness, assurance, and empathy. The measurement quality of service is also influenced by the supporting factors / obstructing (Moenir). This study obtained the results, there are four dimensions tangible, reliability, responsiveness, and assurance that have not run well, there is only one dimension of empathy has been run well. The results of the study can be explained that there are four of six factors that initiative the quality civil registration services (awareness, rules / procedures, organization, and income). On the other hand proportional to the factors that become obstacles such as, the ability / appearance factors of officers who are still requiring training, monitoring, and evaluation periodically as well as the factors of supporting service facilities the main support service that is less in terms of quantity and quality.